GEOTECHNICAL CHARACTERIZATION OF SOILS IN THE CENTER OF DIWANIYAH (IRAQ): EXPERIMENTAL EVALUATION OF PHYSICAL AND MECHANICAL PROPERTIES (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
This paper is a detailed experimental and statistical study on the geotechnical properties of soils collected from more than 15 site locations within the center of Diwaniyah at depths between 1 and 10 m below ground surface. Tests were conducted for grain size distribution, Atterberg limits, compaction characteristics and shear strength parameters in laboratory.Soils mainly clayey–silty alluvium falls in the CL-CI category. The L.L ranges from 44% to 60% and the plasticity index (PI) varies from 20% to 34%. The results of the statistical analysis show that the mean liquid limit and plasticity index are 51.2% and 27.6%, respectively. The coefficient of variance for both parameters is moderate. The maximum dry density ( γd,max ) is in the range of 16.8 and 18.1 kN/m³; the optimum moisture content (OMC) is in the range of 15 to 21 .%Data on the shear strength parameters showed that c values are between 28 and 62 kPa. Likewise, φ values are from 17° to 27°. The findings show average of shear strength and compressibility. The study presents geotechnical parameters that are statistically backed for foundation design in central Iraq.
Keywords: Geotechnical properties; Statistical analysis; Clayey–silty soil; Shear strength; Compaction; Diwaniyah.